Low-grade myofibroblastic sarcoma of maxillary sinus and buccal mucosa: Two rare cases and review of the literature - Anirban Ghosh; Arghya Bandopadhyay; Rajarshi Sarkar (Wolters Kluwer Medknow Publications, 2019)
Low-grade myofibroblastic sarcoma (LGMS) represents an atypical tumor composed of myofibroblasts with a predilection for the head and neck, especially in the tongue and oral cavity, with a high tendency to local recurrence and metastasis, even after a long period. LGMS arising from maxillary sinus and buccal mucosa are not very common. To the best of our knowledge, only 55 cases of low-grade myofibroblastic sarcoma have been reported and only four cases of LGMS of maxillary sinus and three cases of LGMS of buccal mucosa have been reported in world literature. We report two cases of LGMS of the maxillary sinus and buccal mucosa, discussing clinical, histological, inmunohistochemical and therapeutic features.